(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Bioleaching technology (biohydrometallurgy), with its sustainability, low energy consumption, and environmental friendliness, provides an innovative pathway for tailings recycling and low-grade ore processing, making it a research focus in interdisciplinary fields of mining engineering and environmental science. The critical challenge in seawater biohydrometallurgy lies in obtaining highly chloride-tolerant microbial strains and consortia to dissolve valuable metals from solid sulfides, tailings, or electronic waste into the liquid phase for subsequent extraction. This study focuses on seawater-based bioleaching technology, A salt-tolerant acclimated culture system of Acidithiobacillus thiooxidans was established to systematically investigate the coupled effects of pH gradients (3 7) and chloride ion concentrations (0, 2.5, 5, 10, 24 g/L NaCl) on pyrite bioleaching. Additionally, the roles of different sulfur substrates (tetrathionate, thiosulfate, and elemental sulfur) in the system were compared. The results indicated that 10 g/L of NaCl promoted the pyrite bioleaching and tetrathionate was the best substrate. This study demonstrates a possibility for bioleaching practice using seawater.